Irish influence on medieval Welsh literature - Sims-Williams, Patrick (Oxford University Press, 2010)
Patrick Sims-Williams provides an approach to some of the issues surrounding Irish literary influence on Wales, situating them in the context of the rest of medieval literature and international folklore.